Analisis Portofolio Saham Pada Perusahaan Sub Sektor Pertambangan Yang Terdaftar Di Bursa Efek Indonesia (BEI) Dengan Pendekatan Capital Asset Pricing Model (CAPM) dan Arbitrage Pricing Theory (APT) - George Luois David Lento; Imam Nazarudin Latif; Camelia Verahastuti (Journal of Indonesian Science Economic Research, 2019)
The purpose of this study aims to determine the expected return of the stocks at the mining firms by sector that listing in Indonesia’s Stock Exchange with the CAPM & APT method and also to compare which one from those method was best to predict the expected return. The analytical tools used are Capital Asset Pricing Model (CAPM) and Arbitrage Pricing Theory (APT) and also Mean Absolute Deviation (MAD). The results of this study shows : 1) Expected return value of yearly average with CAPM method period 2016 – 2018 is inclined fluctuation with the result that the hypothesis was rejected. 2) Expected Return value of yearly average with APT method period 2016 – 2018 is always decreases with the result that the hypothesis was rejected. 3) MAD value for CAPM method has smaller value than MAD for APT method, it means CAPM was better than APT in predicting expected return, this result is also showed the hypothesis is accepted. The conclusion of this study is : 1) The result shown expected return at the mining firms by sector in period 2016 – 2018 is inclined fluctuationly, the reasons is CAPM use one systematic risk only that is stock value which came from the intern of the firm. 2) The result shown the expected return at the mining firm by sector in period 2016 – 2018 is always decreases significant enough, the reasons is APT use many economic macro factor like inflation, SBI rate, rupiah kurs in which that factor was increasingly in this study period. 3) The result of MAD CAPM after compare with MAD APT has smaller value, it shows CAPM Method was better than APT method in predicting expected return.